1999
DOI: 10.1128/cdli.6.5.768-770.1999
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus DNA in Blood Samples Positive for Antibodies to Core Antigen and Negative for Surface Antigen

Abstract: Anti-hepatitis B core antigen (HBcAg)-positive hepatitis B surface antigen (HBsAg)-negative plasma samples from blood donors were tested by nested PCR. DNA positivity was more significantly associated with high levels of anti-HBcAg than with low levels of anti-HBsAg antibodies. Analysis of a dilution of anti-HBcAg antibodies might result in a more rational exclusion of anti-HBcAg-positive HBsAg-negative samples, reducing the number of donations discarded and enabling more countries to incorporate anti-HBcAg te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
0
8
0
2
Order By: Relevance
“…Blood from such donors has been evaluated and found suitable for transfusion. This not only encourages voluntary blood donation, but also helps in increasing the inventory of blood units available for stocking in the blood bank [15]. In India, however, as the prevalence of anti-HBc is quite high, screening donor blood for anti-HBc total may not be practical.…”
Section: Discussionmentioning
confidence: 99%
“…Blood from such donors has been evaluated and found suitable for transfusion. This not only encourages voluntary blood donation, but also helps in increasing the inventory of blood units available for stocking in the blood bank [15]. In India, however, as the prevalence of anti-HBc is quite high, screening donor blood for anti-HBc total may not be practical.…”
Section: Discussionmentioning
confidence: 99%
“…For example, anti‐HBc only was found in 0·5% of Swiss blood donors and HBV DNA in 3·9% (Grob et al ., 2000), while in Germany, the prevalence was 0·2% for the former and 7·4% for the latter (Grob et al ., 2000). In Venezuela, known to have an intermediate HBV infection frequency, overall anti‐HBc‐positive prevalence in blood donors reported is 4–5%, and HBV DNA has been found in 6% of HBsAg‐negative, anti‐HBc‐positive blood units (Gutierrez et al ., 1999). Finally, a recent study in the USA showed that 0·84% of US blood donors were anti‐HBc positive while manifesting negative on all other routine blood donor screening assays, and HBV DNA was found in 3·7% of the anti‐HBc only positive donors (Kleinman et al ., 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a recent study in the USA showed that 0·84% of US blood donors were anti‐HBc positive while manifesting negative on all other routine blood donor screening assays, and HBV DNA was found in 3·7% of the anti‐HBc only positive donors (Kleinman et al ., 2003). The percentage of HBV DNA observed in the present study is comparable to that reported for Germany (Grob et al ., 2000) and Venezuela (Gutierrez et al ., 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Según estos autores, la implementación de la extracción de ADN por el método fenol-cloroformo con un mayor volumen de muestra, unido al tipo de cebadores utilizado (preferible- mente mediante PCR anidada) aumenta las probabilidades de detectar ADN del VHB en el suero. Estos resultados coinciden con un estudio anterior de los autores, en el cual se observó una mayor frecuencia de detección del ADN del VHB cuando se optimizaron las condiciones de extracción y el volumen de la muestra (13). En el presente estudio se analizaron las combinaciones óptimas de cebadores para la PCR anidada y se confirmó que el método de ultracentrifugación utilizado permitió la recuperación eficiente de partículas virales, compensando el efecto de dilución ocasionado por la mezcla de las muestras.…”
Section: Discussionunclassified
“…En un estudio realizado en Venezuela, previo a la implementación de la determinación de anti-HBc en bancos de sangre, se determinó que la incidencia de hepatitis postransfusional por VHB era de 3,8% (12). Otro estudio realizado recientemente sugirió que alrededor del 10% de las unidades positivas a la prueba de anti-HBc contienen ADN del VHB (13). El descarte de unidades positivas a anti-HBc, así como el perfeccionamiento de los estuches diagnósticos, permiten suponer una reducción significativa en la inci-dencia de hepatitis B postransfusional en el país actualmente, aunque se desconoce la magnitud de la infección silente en la región.…”
Section: Introductionunclassified